Challenges in collecting and using web data in the banking sector - Silonsaari, Emmi (2024)
Digitalization has revamped the marketing landscape rapidly and has changed a lot of business actions to online services. It has become increasingly important for companies to be able to seek knowledge on how their customers are performing within their websites and other digital marketing channels. Therefore, web analytics and tracking are important tools to gain understanding and insights for decision-making and the future development. There are, however, still improvements needed for organizations to be fully data-driven and there are still known challenges in web analytics usage. Moreover, there are regulations impacting the data collection within countries in the European Union. The objective of this study is to focus on researching web analytics as a central component of digital marketing activities in the context of the banking industry. The idea is to increase the awareness and understanding of web data usage and the issues of it within the banking industry, where data involved consists of great amounts of sensitive data. In addition, this study takes place in Finland and as the country is a part of the European Union, it operates under the legislations and regulations within the EU. This study seeks to gain knowledge on the biggest challenges in web data collection and usage, focusing on the banking industry in Finland. Three research questions were created to support the thesis: (1) What is the purpose of using web analytics in banking sector, (2) what the main issues are when collecting web data in a banking sector and, (3) what the main challenges are when analysing web data in a banking sector. A qualitative approach was chosen to support the explorative nature of the research. Interview data of banking industry professionals were collected and analysed with thematic analysis. The findings are consistent with previous research and indicate that the organizations are not as data driven as they think they are. Even though the industry is highly regulated, data is still collected from customers, however, the tools used have some limitations. Moreover, it seems that key performance indicators are not set to guide the data-driven decision-making indicating the data is not used to guide decisions. The findings suggest that the organizations could improve knowledge within the team units towards data collection and tracking. In addition, there could be improvements in the collaboration between teams.